The Surprising Role of Amyloid Fibrils in HIV Infection - James Shorter; Laura M. Castellano (Biology, 2012)
Despite its discovery over 30 years ago, human immunodeficiency virus (HIV) continues to threaten public health worldwide. Semen is the principal vehicle for the transmission of this retrovirus and several endogenous peptides in semen, including fragments of prostatic acid phosphatase (PAP248-286 and PAP85-120) and semenogelins (SEM1 and SEM2), assemble into amyloid fibrils that promote HIV infection. For example, PAP248-286 fibrils, termed SEVI (Semen derived Enhancer of Viral Infection), potentiate HIV infection by up to 105-fold. Fibrils enhance infectivity by facilitating virion attachment and fusion to target cells, whereas soluble peptides have no effect. Importantly, the stimulatory effect is greatest at low viral titers, which mimics mucosal transmission of HIV, where relatively few virions traverse the mucosal barrier. Devising a method to rapidly reverse fibril formation (rather than simply inhibit it) would provide an innovative and urgently needed preventative strategy for reducing HIV infection via the sexual route. Targeting a host-encoded protein conformer represents a departure from traditional microbicidal approaches that target the viral machinery, and could synergize with direct antiviral approaches. Here, we review the identification of these amyloidogenic peptides, their mechanism of action, and various strategies for inhibiting their HIV-enhancing effects.